Development of a high-throughput UHPLC–MS/MS multi-method for the analysis of mycotoxins in plant-based milk alternatives as the basis for risk assessment - Dick, Fabian; Schuster, Maximilian; Schneidemann-Bostelmann, Sarah; Asam, Stefan; Rychlik, Michael (Frontiers in Nutrition, 2026)
Plant-based alternatives to animal-based foods represent a rapidly growing market, as more and more consumers are willing to include these products into their daily diets. One particular segment is plant-based milk alternatives (PBMAs). Environmental and ethical concerns mainly drive this growing trend. However, the raw materials used in the production of PBMAs are susceptible to mycotoxin contamination, and currently, there are no regulatory limits for mycotoxins in PBMAs. Therefore, analyzing PBMAs to get more information about the mycotoxin contamination in these products is of great interest. To obtain more exposure data, we developed a QuEChERS (quick, easy, cheap, effective, rugged, and safe)-based multi-mycotoxin method to analyze 31 Alternaria, Aspergillus, and Fusarium toxins in PBMAs using ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC–MS/MS). The method was successfully validated and applied to 100 different PBMAs from oats, rice, spelt, almonds, hazelnuts, walnuts, cashews, soy, peas, and hemp. Our results showed a frequent contribution of PBMAs to the overall mycotoxin exposure, and some of these products have to be considered critical for toddlers from a risk-assessment perspective. In particular, PBMAs made from oats, almonds, hazelnuts, and tiger nuts were assessed as a risk for this age group.